2020
DOI: 10.1109/access.2020.3015829
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Safety Evaluation of Emergency Training for Building Ruins Scenario Based on Analytic Hierarchy Process-Grey Fuzzy Evaluation

Abstract: The quality of emergency training determines the professional ability of emergency personnel. To evaluate the safety of emergency training for building collapse ruin training scenarios, an approach combining analytic hierarchy process (AHP) and gray-fuzzy evaluation is proposed. According to the characteristics of building collapse ruin training scenarios and the principle of index selection, a safety evaluation index system for this training is constructed from four aspects: human, machine, environment, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…. , ω m ] of secondary risk indicators, and use Formula (9) to calculate the fuzzy comprehensive evaluation vector of secondary risk indicators [37], which is expressed by B b :…”
Section: Fuzzy Comprehensive Evaluationmentioning
confidence: 99%
“…. , ω m ] of secondary risk indicators, and use Formula (9) to calculate the fuzzy comprehensive evaluation vector of secondary risk indicators [37], which is expressed by B b :…”
Section: Fuzzy Comprehensive Evaluationmentioning
confidence: 99%
“…e results show that the constructed model can effectively evaluate the safety evaluation of the training site of building collapse ruins. It has good application practice [4]. Ju et al proposed an EVCS site selection framework in the image fuzzy environment, determined the weight value of the index criterion with the help of the fuzzy analytic hierarchy process, constructed an improved comprehensive graphic fuzzy decision matrix, correlated the ideal value of the site selection site with the grey correlation projection, and found that the proposed framework model can select the appropriate EVCS site among the potential charging stations [5].…”
Section: Related Workmentioning
confidence: 99%
“…In Figure 8, the evaluation membership of evaluation indicators B1-B6 is below 0.1, indicating that they have a good classification effect, and the final score calculation results of indicators are between [3][4][5], and the overall evaluation grade is above good. e above results show that the performance management evaluation based on the GFAHP method has good application efficiency.…”
Section: Application Effect Analysis Of Performance Managementmentioning
confidence: 99%
“…The use of multi-dimensional system indicators in the analysis method will make the results more scientific. There are many methods for the use of establishing a comprehensive evaluation system, including the sensitivity analysis method of grey system theory [6], cluster analysis method [7], analytic hierarchy process [8,9], fuzzy comprehensive evaluation method [10], rough set analytic hierarchy process [11], and factor analysis method [12], etc. Although the above methods introduce the uncertainty of factors in the analysis, there is no random and objective evaluation of the influencing factors of supplier selection.…”
Section: Introductionmentioning
confidence: 99%